2010
DOI: 10.1007/s10439-010-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Attachment–Detachment Control on Temperature-Responsive Thin Surfaces for Novel Tissue Engineering

Abstract: Temperature-responsive intelligent surfaces, prepared by the modification of an interface mainly with poly(N-isopropylacrylamide) and its derivatives, have been investigated. Such surfaces exhibit temperature-responsive hydrophilic/hydrophobic alterations with external temperature changes, which, in turn, result in thermally modulated attachment and detachment with cells. The advantage of this system is that cells cultured on such temperature-responsive surfaces can be recovered as single cells and/or confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 79 publications
0
93
0
Order By: Relevance
“…In the first application, the thermoresponsive ability of the polymers is used to regulate the cells' attachment and detachment from a surface [61][62][63][64]. In fact, in one study, the polymer surface was even reusable for repeated cell culture [65].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…In the first application, the thermoresponsive ability of the polymers is used to regulate the cells' attachment and detachment from a surface [61][62][63][64]. In fact, in one study, the polymer surface was even reusable for repeated cell culture [65].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Also it is essential that the cells are easily detached from the substrate after it has grown. Conventionally enzymatic proteolysis of extracellular matrix (ECM) with trypsin or other proteolytic enzymes used to detach cells from substrates which can affect cell re-adhesion, cell viability etc (Kumashiro et al, 2010). Thermoresponsive polymers are of great interest in tissue engineering applications specifically in cell sheet detachment.…”
Section: Cell Sheet Engineeringmentioning
confidence: 99%
“…[10] Studies have shown that cells attach and therefore proliferate poorly on thick or bulk pNIPAm coatings and many studies report a coating thickness limitation above which there is a 4 dramatic reduction in the number of cells attaching to the polymer surface [12][13][14][15][16]. In studies where pNIPAm was covalently grafted for this purpose, this thickness limitation is in the order of tens of nanometers with the exception of coatings formed via plasma polymerization [12,[17][18][19]. Our previous studies using spin coated commercially sourced polymer found that there was no relationship between the thickness of the film produced and successful cell attachment and proliferation within the thickness-scale employed (> 30 nm to < 2000 nm) [10].…”
Section: This Is Becoming Increasingly Desirable As the Regulatory Bimentioning
confidence: 99%